2017
DOI: 10.1021/acs.macromol.7b02188
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamic Heterogeneity in the Amorphous Phase of Poly(l,l-lactide) Confined at the Nanoscale by the Coextrusion Process

Abstract: Multi-nanolayered Polystyrene/Poly(L,L-lactide) (PS/PLLA) films were obtained by the layermultiplying co-extrusion process, with an individual PLLA layer thickness as thin as 20 nm. The confinement of the amorphous PLLA induced a change in the molecular mobility, evidenced by a drop of the Cooperative Rearranging Region (CRR) size at the glass transition. The annealing of confined PLLA layers revealed slower crystallization kinetics and two-dimensional crystalline growth geometry. Furthermore, the annealing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 68 publications
3
26
0
Order By: Relevance
“…As crystallization proceeds, the organization of the crystal phase slightly improves, which can lead to a decrease in the X RAF / X C ratio in bulk PLLA, as also reported for poly(3-hydroxybutyrate). 64 It is worth noting that a different X RAF / X C evolution has been observed for nanoconfined PLLA, 65 which proves that the crystal/amorphous coupling strongly depends on the geometrical dimensions of the sample under investigation. The present results demonstrate that formation of rigid amorphous fraction is favored at lower crystallization temperatures.…”
Section: Results and Discussionmentioning
confidence: 95%
“…As crystallization proceeds, the organization of the crystal phase slightly improves, which can lead to a decrease in the X RAF / X C ratio in bulk PLLA, as also reported for poly(3-hydroxybutyrate). 64 It is worth noting that a different X RAF / X C evolution has been observed for nanoconfined PLLA, 65 which proves that the crystal/amorphous coupling strongly depends on the geometrical dimensions of the sample under investigation. The present results demonstrate that formation of rigid amorphous fraction is favored at lower crystallization temperatures.…”
Section: Results and Discussionmentioning
confidence: 95%
“…They also reported that MAF dimensions are significantly higher than the characteristic length of the CRR [42], suggesting that the geometrical confinement is not the only cause for the decrease of the CRR size. Nassar et al [82] showed that crystallization of PLLA confined against polystyrene did not induce any variation in the cooperativity length when no RAF was formed, evidencing that the coupling between amorphous and crystal plays a major role in the cooperativity variations.…”
Section: Free Volume and Glass Transition Cooperative Dynamicsmentioning
confidence: 99%
“…The assumption of a confinement effect induced by the crystalline phase seems not satisfying either. Indeed, in the study of Nassar et al [82], the effects of crystallization and coupling have been separated. It has been shown that the crystallization does not systematically impact the cooperativity, whereas the rigidification of the amorphous phase strongly decreases ξ Τα .…”
Section: Free Volume and Glass Transition Cooperative Dynamicsmentioning
confidence: 99%
“…As a consequence, geometrical limitations increase, which maximizes RAF formation. 4,42,47 Despite the uncertainties, it seems that the RAF development in PC/PLLA is independent from the PLLA layer thickness and that more RAF is created at lower temperature. This is the contrary to the results of the PS/PLLA system reported for the annealed 20 nm thick PLLA layers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The experimental setup consisted of two single screw extruders (Rheoscam Scamex, France) of 20 mm with gear pumps, a three-layer feed block (A-B-A), a series of layer-multiplying elements, a flat die, and chill rolls (Scamex, France), as described by our earlier work. 42 The layermultiplying elements cut the flow in half vertically and subsequently superpose, compress, and stretch it to its original width. A series of n elements leads thus to 2 n+1 +1 alternating layers.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%